The Nexus between Economic Growth, Energy Consumption, and Environmental Degradation in Kenya - Hassan Abdikadir Hussein; Abdimalik Ali Warsame; Galad Mohamed Barre; Mohamed Ahmed Salad (International Journal of Energy Economics and Policy, 2023)
Energy is a crucial component of productivity and is regarded as an engine for economic growth. In countries where more energy is consumed, the standard of living is frequently higher. Yet utilizing energy also leads to the emission of harmful greenhouse gases like carbon dioxide emissions (CO2) and sulphur dioxide emissions (SO2). In this regard, this study examines the relationship between economic growth, energy consumption, and environmental degradation in Kenya using the Autoregressive Distributed Lag model (ARDL) from 1990 to 2019. The empirical results find that energy consumption and economic growth increase CO2 emissions both in the short- and long-run in Kenya except for economic growth which is inconsequential in the short run. However, the study suggests the implementation of environmental regulations that would contribute in lowering pollution emissions. In addition, implementing policies that encourage investing in cleaner energy sources will reduce environmental pollution. The Kenyan policymakers should undertake various technological, behavioural, and other changes to increase its economy's overall energy efficiency.